Peningkatan Kemampuan Menyelesaikan Soal Cerita Bilangan Bulat Melalui Penerapan Metode Penggunaan Media Benda-Benda Terdekat Pada Pelajaran Matematika Siswa Kelas Vii Pmds Putra Palopo - Helda Helda; Ino Sulistiani (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2016)
Thiss research implemented by 2 cycles and each cycle implemented in 4 times of the meeting included the last test in every time of the cycle. The data in this research taken for use with result study of test and observation. Each datum which collected in this research analyzed with descriptive analysis. The result of this research achieved after the implementation step of proximate things media during 2 cycles: a) the increasing result mathematics study. Thiss case can see from the increasing average score test and average score see 3 aspects of marking that is draft comprehension, reasoning, and communication achieved with completeness the resultant study in a classical. The first cycle obtained average score test students is 64,44. From 100, is the highest score with standard deviation in the amount of 11,819 and at the second cycle obtained average score 83,11 from 100, is the highest score with deviation standard 8,410. Completeness presentation the result at first cycle is 44,44%. That is 16 from 36 students otherwise complete their study, and the second cycle 100% is 36 from 36 students otherwise complete their study. b) In this research happen attitude change in students about mathematics become better each time during teaching and studying process. From result of this research, we are able to summed up that applied to proximate things media at mathematics learning, then the result of VII SMP PMDS Putra Palopo can rise.